Asymptomatic Bacteriuria among Women Attending the Antenatal Clinics in Jeddah, Western Region of Saudi Arabia - Hanan M. Ali Shamrani, (Journal of King Abdulaziz University: Medical Sciences, 2023)
This retrospective chart review was conducted to determine the proportion of pregnant women with asymptomatic bacteriuria who were followed up at the antenatal clinics of King Abdulaziz University Hospital, Jeddah between January 2007 and January 2012. Clinical and paraclinical data were recorded for 337 women in their last trimester of pregnancy. The prevalence of asymptomatic bacteriuria in the cohort was 31.26%. The most frequently isolated bacteria included Escherichia coli and Klebsiella pneumoniae in 30.39% and 10.78% of the cases, respectively. In most cases, the isolated bacteria were sensitive to ampicillin (11.57%), amoxicillin (10.38%), and amikacin (5.63%). Most bacteria were resistant to nitrofurantoin (21.06%), tetracycline (21.06%) and cefixime (20.77%). The most common prescribed medications included multivitamins (n = 40; 11.87%), vitamin B12 (n = 47; 13.95%), folic acid (n = 45; 13.35%), and antibiotics (n = 43; 12.75%). Overall, it is possible that pregnant women with asymptomatic bacteriuria are undertreated at our institution. Gaps in the management of these patients should be identified to improve patient care.